Evaluation of E-Ticketing Technology in Construction of Highway Projects: A Systematic Review of Adoption Levels, Benefits, Limitations and Strategies - Subramanya, Karthik; Kermanshachi, Sharareh; Pamidimukkala, Apurva (Frontiers in Built Environment, 2022)
Highway and bridge construction projects are subject to cost and schedule overruns, as well as workforce shortages in remote locations, both of which can result in disputes over the quality of the end product. E-ticketing technology can improve the quality, however, while decreasing cost overruns and schedule delays. Despite the benefits of E-ticketing, many state departments and agencies are unwilling to transition into this technology. This study aims to identify the potential barriers to implementing E-ticketing, determine the adoption rate of state agencies/departments, and evaluate the benefits of employing an E-ticketing platform. The changes in technological trends in highway construction that are related to material tracking, inspection, and digitization are qualitatively analyzed, using meta-synthesis and interpretative analytical techniques. Key technologies that have the potential to be integrated into the E-ticketing platform to mitigate the limitations faced at the time of implementation are also discussed. The study’s findings suggest that the implementation process and regulations of an E-ticketing platform vary drastically from state to state, and a common set of guidelines is essential for obtaining long term success. The study advocates four key recommendations for widespread implementation of the E-ticketing platform and suggests directions for further research. The results of this study will assist DOT’s decision-makers and engineers in developing a common E-ticketing platform, adopting policies and guidelines, decreasing the costs of their projects, providing the initial investment, running pilot tests, enhancing the safety of their inspectors, and completing their projects in a timely and efficient manner.